Особенности феномена музыки как объекта мышления - Донец, Иван; Donets, Ivan (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статье произведен краткий анализ феномена музыки как особой сферы впечатлений. Философско-метафизический момент восприятия музыки как мышления нашел интересную интерпретацию, которая выхо-дит на определение музыки как выводящую за пределы априорных форм опыта. Отсюда новый термин – деаприор. Короткое обоснование метафизических аспектов философии музыки в данном исследовании допол-няется эмотико-субьективными недо-сказами. Мышление и «Я» оказались взаимозависимой составной сферы знания. The article made a brief analysis of the phenomenon of music as a special sphere of experience. Philosophical-metaphysical moment of perception of music as thinking, found an interesting interpretation, which goes to the definition of music as beyond the limits of a priori forms of experience. Hence the new term − deaprior. A short study of metaphysical aspects of the philosophy of music in this study supplemented by subjective emotional under-tales. Thinking and “I” were interdepen-dent composite spheres of knowledge. Attempts to clarify the co-self-knowledge, or knowledge of the “I”, ancient as the world. Genesis and the life of the heavenly bodies visibly correspond audible rhythm and harmony of the universe (Schelling). Music, therefore, could not be better virtualizes the objective component of our subjective pole. Modulating the three modes of time, the music goes into the category of the object with his (on the subject) analogue experience
Features of the Phenomenon of Music as an Object of Thought
Keywords: «Я»; “I”; музыка; the music; мышление; thinking; деаприор; deaprior